Self-assembly of heterobimetallic d-f hybrid complexes: sensitization of lanthanide luminescence by d-block metal-to-ligand charge-transfer excited states. - Pope, S; Coe, B; Faulkner, S; Bichenkova, E; Yu, X; Douglas, K (2004)
Carboxylate-bearing d-transition metal bipyridyls form ternary complexes with seven-coordinate lanthanide centers. The neodymium,- ytterbium-, and erbium-containing complexes exhibit lanthanide-centered emissions sensitized by the MLCT states of the d-block components.